Pendidikan THE ROLE OF VOWEL SOUND IN ENGLISH PRONOUNCIATION : THE ROLE OF VOWEL SOUND IN ENGLISH PRONOUNCIATION - wahyu, milda; Suhaida Zain Panjaitan; Yani Lubis (Cendekia Madani Nusantara, 2024)
This journal explores the role of vowel sounds in linguistic structures and communication, focusing on English pronunciation. It uses phonetic and phonological approaches to understand how vowel sound quality affects communication. The study provides insights into how vowel sound differences affect perception and interpretation. It also highlights the implications for language learning, particularly improving English learners' pronunciation. The journal aims to develop teaching strategies to help learners overcome difficulties in producing appropriate vowel sounds, enriching the learning experience. This journal examines the role of vowel sounds in linguistics and phonetics, focusing on their frequency, duration, and quality. It also examines their impact on language learning, suggesting that understanding vowel sound phonetics can improve pronunciation and comprehension skills. The findings can guide the development of effective teaching methods and resources for native speakers and learners, thereby supporting the development of linguistic curricula and teaching methods that cater to diverse communicative needs